Effects of processing parameters on production of graphene by mechanical exfoliation - Muhamad Zarif, Anuar (2017)
Graphene, a monolayer form of carbon with two dimensional honeycomb lattices (sp2 Hybridization) has shown excellent mechanical, electrical, thermal and optical properties. It is a promising component for many applications in the fields of electronics, composites, sensors as well as energy storage and conversion devices. These engineering applications require availability of graphene on the mass scale and thus suitable processes are necessary for its production down to few sheets level. In the present work, the objective is to study the effect of processing parameter on preparation of graphene at large scale by liquid phase exfoliation of graphite assisted by ultra sound to promote the intercalation and expansion of graphite by using homogenizer. Water and tea polyphenol was choose and act as a dispersion agent and antioxidant. From the result, it is found that the graphene dispersion concentration is increased when the sonication time and power increased with the highest concentration of 1.0699 mg/ml. But, by controlling the centrifuged speed, the result shows no influenced on dispersion concentration. In Addition, the size of the sheets also become smaller when increasing sonication time and power. However, from the XRD analysis, it can be conclude that the graphite only partially exfoliated with the stack of several or tens of single layer graphite. Therefore, by controlling LPE critical parameter likes sonication power, sonication time and centrifuged speed, graphene can produce at high scale.